Comparison of 2D Shear Wave Elastography, Transient Elastography, and MR Elastography for the Diagnosis of Fibrosis in Patients With Nonalcoholic Fatty Liver Disease - Furlan, Alessandro; Tublin, Mitchell E; Yu, Lan; Chopra, Kapil B; Lippello, Anita; Behari, Jaideep (American journal of roentgenology (1976), 2020)
The aim of the present study was to compare the diagnostic accuracy of liver stiffness measurements (LSMs) obtained using MR elastography (MRE), transient elastography (TE), and 2D shear wave elastography (SWE) in patients with biopsy-proven nonalcoholic fatty liver disease (NAFLD). We prospectively enrolled 62 adult subjects (mean age [± SD], 50 ± 13 years; 58% women; body mass index [weight in kilograms divided by the square of height in meters], 35 ± 7). Two-dimensional SWE, MRE, and TE were performed at a mean of 105 ± 86 days after liver biopsy. The area under the ROC curve (AUROC) values and 95% CIs for the corresponding LSMs (expressed in kilopascals) were calculated, with significant fibrosis (Metavir liver fibrosis score, F2-F4) and advanced fibrosis (F3-F4) used as outcome measures. Pairwise comparisons of AUROC values were conducted using the DeLong test. Statistical significance was set at < 0.05. For the 62 subjects, valid LSMs were obtained for 57 subjects with the use of 2D SWE, for 59 subjects with TE, for 59 subjects with MRE, and for 54 subjects with all three modalities combined. The AUROC values (95% CIs) of 2D SWE, TE, and MRE for the diagnosis of significant fibrosis were 0.80 (0.67-0.92), 0.77 (0.64-0.89), and 0.85 (0.74-0.95), respectively. The AUROC values (95% CIs) of 2D SWE, TE, and MRE for the diagnosis of advanced fibrosis were 0.89 (0.80-0.98), 0.86 (0.77-0.95), and 0.95 (0.89-1.00), respectively. Pairwise comparisons revealed similar diagnostic accuracy for significant fibrosis (2D SWE vs MRE, = 0.431; 2D SWE vs TE, = 0.317; and MRE vs TE, = 0.052) and advanced fibrosis (2D SWE vs MRE, = 0.348; 2D SWE vs TE, = 0.293; and MRE vs TE, = 0.059). For patients with biopsy-proven NAFLD, 2D SWE, MRE and TE exhibited comparable and very good to excellent diagnostic accuracy for advanced fibrosis and comparable but lower accuracy for significant fibrosis.